Constructing the good mother: Patriarchal control in Jessamine Chan’s The School for Good Mothers - Sandy Tahniah; Rini Susanti Wulandari (Universitas Negeri Semarang, 2025)
This research is driven by the need to see motherhood as a social construct shaped by patriarchal norms—often tied to women and loaded with unrealistic expectations—while feminist perspectives push back, pointing to how the state plays a key role in controlling and judging mothers. Jessamine Chan's novel The School for Good Mothers has been analyzed from various perspectives, but it has rarely been studied explicitly through Adrienne Rich's concept of institutional motherhood. This study aims to analyze how the state shapes, supervises, and punishes motherhood through visible institutions, such as mentorship, and its impact on agency, identity, and mother-child relations, focusing on the main character, Frida Liu. This study employs a qualitative and descriptive approach, utilizing content analysis through close reading. Data were categorized into three domains of patriarchal control: surveillance, evaluation and punishment, and ideal motherhood standards. Results show Frida experiences four forms of oppression: state control, inner conflict, identity erasure, and emotional disconnection. This study offers insight into feminist literary criticism by demonstrating that motherhood in fiction can be employed as a tool of patriarchal control while reminding us of the importance of viewing mothers as whole human beings in social policy and cultural representation.